EFFECT OF DSB DNA REPAIR MECHANISMS ON CHROMATIN MOBILITY - Sanaullah, Sarvath Aafreen (Wake Forest University, 2021)
Nuclear DNA of eukaryotes is compactly packaged with histone proteins to form chromatin. Chromatin organization and the constant motion of the DNA may regulate genomic functions like gene expressions, DNA synthesis, and DNA repair. Two major pathways are used for the repair of DNA double-strand breaks (DSB): non-homologous end joining (NHEJ) and homologous recombination (HR). The reciprocal dependencies of repair by HR and NHEJ and chromatin mobility are largely unknown in higher eukaryotes. We are characterizing these dependencies using osteosarcoma cells coexpressing histone H2A tagged with photoactivable GFP (PAGFP-H2A) and a DNA damage sensor (mCherry-53BP1). Cells are treated with DSB-causing agents like mitomycin C and bleomycin after specific inhibition of either the DSB repair pathway by a RAD51 inhibitor (HR) or a DNA-PK inhibitor (NHEJ). Also, we use siRNA-based inhibition of NHEJ as a complementary approach to manipulate DSB repair pathway usage. Motions of chromatin microdomains (PAGFP-H2A) are captured using structured illumination with a diffractive optical element. The system produces a 7x7 array of photoactivated chromatin spots. Motions of the 49 spots are captured with time-lapse imaging and particle tracking and related to DNA damage presence (mCh-53BP1). Here, we present validation of the approach and preliminary results on chromatin dynamics in HR vs. NHEJ repair. We find that the chromatin motions when NHEJ is inhibited was not different but surprisingly when HR is inhibited, the global chromatin mobility increases in the absence of DNA damage compared to untreated cells. We also find that chromatin mobility is faster at the break sites compared to non-break sites. For further investigation on the effect of these DSB repair pathways and their effects on chromatin dynamics, cell cycle guided analysis will be required. Indeed, HR repair is mostly restricted to the S phase of the cell cycle. To this end, we have implemented a novel method to select cells in the S phase for live cell cycle analysis. This approach will be used for the continuation of this project.